2014
DOI: 10.1002/admi.201400066
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Nanoimaging of Photoinduced Charge Separation at the Plasmonic Au Nanoparticle‐TiO2 Interface

Abstract: Nb-doped rutile TiO 2 (100), unless otherwise noted) in the presence of a Na [AuCl 4 ] aqueous solution mixed with ethanol (refer to SI for details of the experiments). Electrons in the TiO 2 valence band (VB) are excited by UV light to the conduction band (CB), and holes are generated in the VB. Au 3+ ions are reduced to Au NPs by the excited electrons, and ethanol, a sacrifi cial electron donor, is oxidized by the holes simultaneously. In addiation to polydisperse spheroids (diameter ≈20-110 nm, height/diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 31 publications
(32 reference statements)
0
72
1
Order By: Relevance
“…Those photoelectrochemical responses were highly reproducible for on-off cycles. These results suggest that PICS is caused at the Au-TiO 2 interface, as is the case for metal nanoparticle PICS; 28 electrons are transferred from photoexcited Au semishells to conduction band of the TiO 2 layer. On the other hand, Au-coated flat TiO 2 electrode without SiO 2 @TiO 2 spheres showed very small responses because of no significant absorption in the wavelength range examined.…”
mentioning
confidence: 74%
“…Those photoelectrochemical responses were highly reproducible for on-off cycles. These results suggest that PICS is caused at the Au-TiO 2 interface, as is the case for metal nanoparticle PICS; 28 electrons are transferred from photoexcited Au semishells to conduction band of the TiO 2 layer. On the other hand, Au-coated flat TiO 2 electrode without SiO 2 @TiO 2 spheres showed very small responses because of no significant absorption in the wavelength range examined.…”
mentioning
confidence: 74%
“…9,37 In contrast, anodic photocurrents flow when nanoparticles are deposited on a TiO 2 electrode. 35,38 These results indicate that PICS is based on electron transfer 39 from the plasmonic nanoparticle to TiO 2 . PICS attracts much attention, because of its wide range of applications.…”
Section: Stabilization Of Plasmonic Metal Nanoparticlesmentioning
confidence: 83%
“…We reported PICS for the first time 2 and indicated that it involves electron transfer from the plasmonic NPs to the semiconductor. [2][3][4][5][6][7] The electron transfer involved is explained in terms of external photoelectric effect, hot electron injection, or interfacial electron transition, and recently some groups call it plasmonic hot electron (or carrier) injection. PICS has been widely applied to photovoltaics, 2,[8][9][10][11][12] photocatalysis, 2,13,14 photochromism, [15][16][17] photoactuation, 18 and chemical sensing.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of plasmonic NPs have been used for PICS such as nanospheres, 20 nanoplates, 7 and halfshell arrays. 21 NPs prepared by photocatalytic deposition 2 or thermal dewetting of an evaporated film 9 are suitable for PICS because of direct contact with the semiconductor, while chemically synthesized NPs may exhibit lower charge separation efficiency since they are covered with a protective agent.…”
mentioning
confidence: 99%